Thermoplastic resin composition and molded article
By reasonably preparing the diene graft copolymer, acrylic graft copolymer, and copolymer of vinyl cyanide compound and aromatic vinyl compound in the thermoplastic resin composition, and adding polyester elastomer, the problem of insufficient chemical resistance when using eco-friendly foaming agents is solved, and higher chemical resistance and the same physical properties are achieved.
Patent Information
- Application Number
- CN202210137591.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2015-12-10
- Filing Date
- 2016-11-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2036-11-30
AI Technical Summary
When using an eco-friendly foaming agent, it is difficult for the conventional thermoplastic resin composition to maintain the same impact strength, gloss and vacuum moldability as the traditional resin composition, and at the same time it has higher chemical resistance.
A matrix resin consists of more than 0% to 35% by weight of a diene graft copolymer, more than 0% to 30% by weight of acrylic graft copolymer and 35% to 85% by weight of a copolymer of vinyl cyanide compound and aromatic vinyl compound, and more than 1 part by weight of a polyester elastomer having a melt index of 0.1 to 10 g/10 min is added.
It has achieved the chemical resistance to eco-friendly foaming agents while maintaining the impact strength, gloss and vacuum moldability unchanged, and is suitable for refrigerator inner shells and other applications.
Smart Images

Figure BDA0003504984440000121
Abstract
Description
[0001] This application is a divisional application. The international application number of the original application is PCT / KR2016 / 013917, the application date is November 30, 2016, the application number of the Chinese national phase is 201680007785.2, and the name of the invention is “Thermoplastic resin composition and molded product”. Technical Field
[0002] [CROSS-REFERENCE TO RELATED APPLICATIONS]
[0003] This application claims the benefit of priority from Korean Patent Application No. 10-2015-0175538 filed on December 10, 2015, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference.
[0004] The present invention relates to a thermoplastic resin composition and a molded article prepared therefrom. More particularly, the present invention relates to a thermoplastic resin composition for an inner shell of a refrigerator, which provides higher chemical resistance to a blowing agent while providing the same impact strength, glossiness and vacuum formability as existing resin compositions, and a molded article prepared therefrom. Background Art
[0005] Typically, cyclic fluorocarbons (CFCs) such as CCl3F (CFC-11) have been used as standard blowing agents for the preparation of rigid and flexible polyurethane and isocyanate foams. However, their use is controlled due to the destruction of the ozone layer in the stratosphere caused by the release of the substance into the atmosphere. Therefore, it has been proposed to use hydrogen-containing chlorofluorocarbons (HCFCs) such as CHCl2CF3 (HCFC-123) and CH2ClCHClF (HCFC-141b) which have a relatively short life span in the atmosphere as alternative blowing agents. However, some chlorinated HCFCs also have relatively high global warming potentials (GWP) and ozone depletion potentials (ODP).
[0006] Therefore, chlorine-free partially hydrogenated fluorocarbons (HFCs) have been proposed as blowing agents to replace HCFC compounds. However, since HCF has problems such as relatively high inherent thermal conductivity, i.e., low thermal insulation performance, HFC-based blowing agents with improved thermal insulation performance, such as CF3CH2CF2H (HFC-245fa), have been proposed. However, HFC-based blowing agents such as HFC-245fa and the recently developed HFC-134a and HFC-365mfc also have the disadvantage that their global warming index is higher than the ideal global warming index.
[0007] In addition, although hydrocarbon blowing agents such as isopentane and n-pentane or cyclopentane show very low global warming index, for example, hydrocarbon blowing agents have lower insulation efficiency than HFC-245fa as a blowing agent, and are flammable.
[0008] When polyurethane is foamed to provide a polyurethane foam layer, the above-mentioned foaming agent is used. The obtained polyurethane foam is used as a heat insulating substance between an outer steel plate and a molded inner resin of a refrigerator component.
[0009] As a substance for molding the inner resin, acrylonitrile-butadiene-styrene resin (hereinafter referred to as "ABS resin") which has excellent processing properties, molding properties, impact resistance, strength, glossiness, etc. and is widely used in various electrical and electronic parts and accessories can be used. Such acrylonitrile-butadiene-styrene resin should have excellent chemical resistance that is not deteriorated by the above-mentioned foaming agent, thereby preventing defects such as cracks from being generated during the production process and the use of the product.
[0010] Therefore, in order to improve the chemical resistance of ABS resin, various methods have been tried, such as a method of increasing the content of acrylonitrile contained in ABS resin, a method of increasing the molecular weight of the resin, a method of increasing the content of butadiene rubber, a method of using a product containing rubber with a larger average diameter, and a method of using acrylic rubber. However, due to the development of a foaming agent having new eco-friendly characteristics and improved foaming efficiency, it is difficult to provide a thermoplastic resin composition for a refrigerator inner shell having a more stringent level of chemical resistance while maintaining the same impact strength, glossiness, vacuum formability, etc. as the existing ABS resin.
[0011] [Related technical literature]
[0012] [Patent Document]
[0013] (Patent Document 1) KR 10-2000-0014170 A
[0014] (Patent Document 2) KR 10-2006-0076161 A Summary of the invention
[0015] Technical issues
[0016] Therefore, the present invention has been made in view of the above problems, and an object of the present invention is to provide a thermoplastic resin composition which, when used to manufacture an inner shell of a refrigerator, provides higher chemical resistance to a blowing agent, especially a recently developed eco-friendly blowing agent, while providing the same impact strength, glossiness and vacuum formability as existing resin compositions.
[0017] Another object of the present invention is to provide a molded article which, when used to manufacture an inner shell of a refrigerator, provides higher chemical resistance to a blowing agent, particularly a recently developed eco-friendly blowing agent, while providing the same impact strength, glossiness and vacuum formability as the existing resin composition.
[0018] The above-mentioned objects and other objects can be achieved by the present disclosure described below.
[0019] Technical Solution
[0020] According to one aspect of the present invention, there is provided a thermoplastic resin composition, comprising: 100 parts by weight of a base resin, the base resin comprising greater than 0% by weight to 35% by weight of a diene graft copolymer, greater than 0% by weight to 30% by weight of an acrylic graft copolymer, and 35% by weight to 85% by weight of a copolymer of a vinyl cyanide compound and an aromatic vinyl compound; and
[0021] More than 1 part by weight of a polyester-based elastomer having a melt index (230° C., 2.16 kg) of 0.1 to 10 g / 10 min.
[0022] According to another aspect of the present invention, provided is a molded article including the thermoplastic resin composition.
[0023] Beneficial Effects
[0024] As is apparent from the above description, the present invention advantageously provides a thermoplastic resin composition and a molded article prepared therefrom, which, when used to manufacture an inner shell of a refrigerator, provides higher chemical resistance to a blowing agent while providing the same impact strength, gloss and vacuum formability as existing resin compositions. DETAILED DESCRIPTION
[0025] Hereinafter, the present invention is described in detail.
[0026] The present inventors have confirmed that when a foam sheet made of a foaming agent having an ozone depletion potential (ODP) of 0 is mixed with an acrylic rubber other than a diene rubber and contains a specific polyester-based elastomer to apply the foam sheet to a base material of an inner shell, a more stringent level of chemical resistance is achieved and the same impact strength, glossiness and vacuum formability as those of the existing inner shell are provided, thereby completing the present invention.
[0027] Hereinafter, the thermoplastic resin composition according to the present invention is described in detail.
[0028] The thermoplastic resin composition according to the present invention comprises: 100 parts by weight of a base resin, wherein the base resin comprises from more than 0 to 35 weight % of a diene graft copolymer, from more than 0 to 30 weight % of an acrylic graft copolymer and from 35 to 85 weight % of a copolymer of a vinyl cyanide compound and an aromatic vinyl compound; and more than 1 part by weight of a polyester elastomer having a melt index (230° C., 2.16 kg) of 0.1 to 10 g / 10 min.
[0029] The diene graft copolymer may be, for example, a copolymer prepared by graft-polymerizing 30 to 70 wt % of a diene rubber-like polymer; and 30 to 70 wt % of an aromatic vinyl compound and a vinyl cyanide compound in total. Within the range, impact strength, glossiness, and vacuum formability are improved without affecting chemical resistance.
[0030] As another example, the diene-based graft copolymer may be a copolymer prepared by graft-polymerizing 35 to 65 wt % of a diene-based rubbery polymer; and 35 to 65 wt % in total of an aromatic vinyl compound and a vinyl cyanide compound.
[0031] The content of the vinyl cyanide compound in the aromatic vinyl compound and the vinyl cyanide compound (hereinafter referred to as "compounds") may be, for example, 20 to 40 wt% or 25 to 35 wt%, based on 100 wt% of the total of the compounds. Within the above range, impact strength, gloss, vacuum formability and chemical resistance are improved.
[0032] The aromatic vinyl compound of the present disclosure may be, for example, one or more selected from the group consisting of styrene, α-methylstyrene, o-ethylstyrene, p-ethylstyrene, and vinyltoluene.
[0033] The vinyl cyanide compound of the present disclosure may be, for example, one or more selected from acrylonitrile, methacrylonitrile, and ethacrylonitrile.
[0034] The average particle size of the diene rubber-like polymer may be, for example, 0.2 to 0.4 μm. Preferably, the average particle size of the diene rubber-like polymer is 0.25 to 0.35 μm. In this case, impact strength, glossiness, vacuum formability, and chemical resistance are improved.
[0035] The diene rubber polymer can be prepared, for example, by polymerizing a conjugated diene compound. The conjugated diene compound can be, for example, one or more selected from 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and isoprene. Preferably, the diene rubber polymer is 1,3-butadiene.
[0036] The diene-based graft copolymer may be included in an amount of, for example, 5 to 35 wt % or 10 to 35 wt % based on 100 wt % of the base resin Within the above range, impact strength, glossiness, and vacuum formability are improved without affecting chemical resistance.
[0037] The acrylic graft copolymer may be, for example, a copolymer prepared by graft-polymerizing 30 to 70 wt % of an acrylic rubber-like polymer; and 30 to 70 wt % of an aromatic vinyl compound and a vinyl cyanide compound in total. Within the range, chemical resistance is improved without affecting impact strength, glossiness, and vacuum formability.
[0038] Preferably, the acrylic graft copolymer is a copolymer prepared by graft-polymerizing 35 to 65 wt % of an acrylic rubber-like polymer; and 35 to 65 wt % in total of an aromatic vinyl compound and a vinyl cyanide compound.
[0039] The content of the vinyl cyanide compound in the aromatic vinyl compound and the vinyl cyanide compound (hereinafter referred to as "compounds") may be, for example, 20 to 40 wt% or 25 to 35 wt%, based on 100 wt% of the total of the compounds. Within the above range, impact strength, gloss, vacuum formability and chemical resistance are improved.
[0040] The average particle size of the acrylic rubber-like polymer may be, for example, 0.3 to 0.6 μm. Preferably, the average particle size of the acrylic rubber-like polymer is 0.35 to 0.55 μm. In this case, impact strength, glossiness, vacuum formability, and chemical resistance are effectively improved.
[0041] Acrylic rubber polymer can be formed by, for example, polymerizing acrylate monomers. The acrylate monomers can be, for example, alkyl acrylates having 2 to 8 carbon atoms. As a specific example, the acrylate monomers can be selected from methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, tert-butyl acrylate, n-butyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, tert-butyl methacrylate, n-butyl methacrylate, n-octyl methacrylate and 2-ethylhexyl methacrylate. Preferably, the acrylate monomer is n-butyl acrylate or n-butyl methacrylate.
[0042] The acrylic graft copolymer may be included in an amount of, for example, 5 to 30 wt % or 5 to 20 wt % based on 100 wt % of the base resin Within the range, chemical resistance is improved without affecting impact strength, vacuum formability, and glossiness.
[0043] The copolymer of the vinyl cyanide compound and the aromatic vinyl compound may be, for example, a copolymer prepared by polymerizing 55 to 95 wt % of an aromatic vinyl compound and 5 to 45 wt % of a vinyl cyanide compound. Within the above range, molding properties required for processing into a base resin and chemical resistance and rigidity required for application to a product may be provided.
[0044] As another example, the copolymer of the vinyl cyanide compound and the aromatic vinyl compound may be a copolymer prepared by polymerizing 60 to 90 wt % of the aromatic vinyl compound and 10 to 40 wt % of the vinyl cyanide compound.
[0045] The copolymer of the vinyl cyanide compound and the aromatic vinyl compound may be, for example, a bulk polymer, an emulsion polymer or a suspension polymer.
[0046] The vinyl cyanide compound-aromatic vinyl compound copolymer may be included in an amount of, for example, 35 to 85 wt % or 38 to 80 wt % based on 100 wt % of the base resin Within the above range, chemical resistance may be improved without affecting impact strength and gloss.
[0047] The polyester elastomer may be, but is not limited to, prepared by solid state polymerization of a resin prepared by melt polymerization of an aromatic dicarboxylic acid or its ester-forming derivative, an aliphatic diol, and a polyalkylene oxide. In this case, the Shore hardness of the polyester elastomer may be 35 to 55D or 40 to 50D, and the melt index (MI) may be 0.1 g / 10min to 10 g / 10min or 1 g / 10min to 10 g / 10min. Here, the weight (g) is measured at 230°C and a load of 2.16 kg for 10 minutes according to ASTM D1238. Within the range, chemical resistance is improved without affecting extrusion process and vacuum formability.
[0048] The aromatic dicarboxylic acid may be, for example, one or more selected from terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, and 1,4-cyclohexane dicarboxylic acid.
[0049] The ester-forming derivative of the aromatic dicarboxylic acid may be, for example, one or more selected from dimethyl terephthalate, dimethyl isophthalate, dimethyl 2,6-naphthalene dicarboxylate and dimethyl 1,4-cyclohexane dicarboxylate. Preferably, the ester-forming derivative is dimethyl terephthalate.
[0050] The content of the aromatic dicarboxylic acid or its ester-forming derivative may be, for example, 25 to 65 wt % based on the total weight of the polyester elastomer. The content of the aromatic dicarboxylic acid or its ester-forming derivative is preferably 35 to 65 wt % based on the total weight of the polyester elastomer. Within the range, an excellent reaction balance is exhibited, thereby allowing the reaction to proceed smoothly.
[0051] The molecular weight of the aliphatic diol can be 300g / mol or less. As a specific example, the aliphatic diol can be one or more selected from ethylene glycol, propylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, etc. Preferably, the aliphatic diol can be 1,4-butylene glycol. Based on the gross weight of the thermoplastic polyester elastomer, the content of the aliphatic diol can be 20 wt % to 40 wt %. Preferably, based on the gross weight of the thermoplastic polyester elastomer, the content of the aliphatic diol can be 2 wt % to 35 wt %. Within the range, an excellent reaction balance is exhibited, so that the reaction proceeds smoothly.
[0052] The polyalkylene oxide may constitute, for example, a soft segment in the form of an aliphatic polyether. As a specific example, the polyalkylene oxide may be one or more selected from polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyhexamethylene glycol, a copolymer of ethylene oxide and propylene oxide; an ethylene oxide addition polymer of polypropylene glycol; a copolymer of ethylene oxide and tetrahydrofuran, etc. Preferably, the polyalkylene oxide is polytetramethylene glycol.
[0053] The content of the polyalkylene oxide may be, for example, 10 to 50 wt % based on the total weight of the thermoplastic polyester elastomer. Preferably, the content of the polyalkylene oxide is 15 to 45 wt % based on the total weight of the thermoplastic polyester elastomer. When the content of the polyalkylene oxide is less than 10 wt %, the hardness of the obtained thermoplastic polyester elastomer is too high, so that the toughness is unsatisfactory. When the content of the polyalkylene oxide is greater than 50 wt %, the heat resistance, compatibility, etc. of the obtained thermoplastic polyester elastomer are unsatisfactory.
[0054] The number average molecular weight of the polytetramethylene glycol is preferably 600 to 3,000 g / mol, more preferably about 2,000 g / mol. Within the range, stable polymerization and properties of the polymerized copolymer are obtained.
[0055] For reference, the hardness of an elastomer is generally expressed as Shore hardness (Shore D), and can be determined according to the content of polyalkylene oxide.
[0056] When the elastomer is prepared by polymerization, a branching agent or the like may be used. When a branching agent is used, the melt viscosity and melt tension of the prepared elastomer may be increased.
[0057] The branching agent can be, for example, selected from one or more of glycerol, pentaerythritol, trimellitic anhydride, trimellitic acid, trimethylolpropane and neopentyl glycol. Preferably, the branching agent is trimellitic anhydride. Based on the gross weight of the thermoplastic polyester elastomer, the content of the branching agent can be, for example, 0.05 wt % to 0.1 wt %. When the content of the branching agent is less than 0.05 wt %, it is difficult to achieve an increase in the melt viscosity of the elastomer obtained. When the content of the branching agent is greater than 0.1 wt %, the polymerization degree of the elastomer obtained is excessively increased, thereby being difficult to control melt polymerization and being difficult to discharge the generated resin.
[0058] There is no particular limitation on the melt polymerization as long as it is a conventional melt polymerization for preparing a thermoplastic polyester elastomer. As a specific example, a catalyst titanium butoxide is added to a starting material consisting of an aromatic dicarboxylic acid, an aliphatic diol and a polyalkylene oxide, and then a transesterification reaction is performed at 140° C. to 215° C. for about 120 minutes, thereby preparing a bis(4-hydroxybutyl) terephthalate (BHBT) oligomer. The prepared BHBT oligomer is added to the catalyst titanium butoxide again, and then polycondensed (about 120 minutes) until the melt index (MI) according to ASTM D1238 reaches 20 g / 10 min (230° C., 2.16 kg), while the pressure is gradually reduced from 760 torr to 0.3 torr at 215° C. to 245° C. Subsequently, the product produced in the reactor is discharged using pressurized nitrogen, and then granulated. Finally, a granular thermoplastic polyester elastomer is obtained.
[0059] The solid-state polymerization is characterized in that the thermoplastic polyester elastomer prepared by melt polymerization is fed into a solid-state polymerization reactor and then polymerized for 10 to 24 hours until the melt index (MI) according to ASTM D1238 reaches 15 g / 10 min (230° C., 2.16 kg) or less, preferably 10 g / 10 min (230° C., 2.16 kg) or less, while gradually reducing the pressure at about 140° C. to 200° C. and under high vacuum in an inert gas stream. Through such solid-state polymerization, a thermoplastic polyester elastomer with high viscosity can be prepared.
[0060] The solid state polymerization reactor may be a vacuum vessel dryer including a high vacuum rotatable pump connected thereto, etc. The inert gas stream may be a nitrogen stream, etc.
[0061] The polyalkylene oxide may be, for example, poly(tetramethylene ether) glycol, or poly(tetramethylene ether) glycol having a molecular weight of 600 to 3,000 g / mol, or polypropylene glycol terminated by ethylene oxide. Preferably, the molecular weight of the polyalkylene oxide is 2,000 to 3,000 g / mol. Within the range, appropriate polymerization reactivity and performance can be achieved.
[0062] The polyester-based elastomer used in the present disclosure may be, for example, commercially available KEYFLEX BT 2140D (DSC melting point: 198° C., Shore A hardness: 95, Shore D hardness: 43, produced by LG Chemistry) or the like.
[0063] The polyester elastomer may be included in an amount of, for example, greater than 1 part by weight, greater than 1 part by weight to 20 parts by weight, 1 to 10 parts by weight, or 3 to 10 parts by weight, based on 100 parts by weight of the base resin. Within the above range, the chemical resistance of the foaming agent, especially the eco-friendly foaming agent, is improved, and the surface gloss, impact strength, and vacuum formability are maintained.
[0064] The thermoplastic resin composition may also contain, for example, one or more selected from antimicrobial agents, heat stabilizers, antioxidants, mold release agents, light stabilizers, inorganic additives, surfactants, coupling agents, plasticizers, compatibilizers, lubricants, antistatic agents, colorants, pigments, dyes, flame retardants, flame retardant aids, anti-drip agents, weathering agents, ultraviolet absorbers and sunscreens.
[0065] The thermoplastic resin composition of the present disclosure can be used as, for example, a substrate of a polyurethane foam sheet. Here, the polyurethane foam sheet can be, for example, a sheet foamed using only a blowing agent containing a fluoroolefin compound having 2 to 6 carbon atoms and having a global warming potential (GWP) of less than 7 and an ozone depletion potential (ODP) of 0, or a sheet foamed using a mixture containing the blowing agent. Here, the mixture of the blowing agent can be 141b, 245fa, cyclopentene, etc.
[0066] As another example, the blowing agent may include a fluoroolefin compound having 3 to 5 carbon atoms. Preferably, the blowing agent includes a compound represented by the following Formula 1:
[0067] [Formula 1]
[0068] XCF2R 3-Z
[0069] wherein X is an unsaturated, substituted or unsubstituted free radical of C1, C2, C3, C4 or C5, each R is independently Cl, F, Br or H, and z is 1 to 3.
[0070] For example, the compound represented by Formula 1 may have at least four halogen substituents. At least three of these substituents may be F.
[0071] As another example, the compound represented by Formula 1 has three to five fluorine substituents. The compound may have substituents such as propylene, butene, pentene, and hexene.
[0072] As another example, the propylene is preferably tetrafluoropropylene or fluorochloropropylene, more preferably CF3CH=CHCl (HFO-1233zd) or CF3CH=CHF (HFO-1234ze).
[0073] The expressions "HFO-1233zd" and "HFO-1234ze" are used to refer to 1-chloro-3,3,3-trifluoropropene and 1,3,3,3-tetrafluoropropene, respectively, regardless of cis or trans. Thus, the expression "HFO-1233zd" refers to cis-HFO-1233zd, trans-HFO-1233zd, and all combinations thereof, and the expression "HFO-1234ze" refers to cis-HFO-1234ze, trans-HFO-1234ze, and all combinations thereof.
[0074] For example, HFO-1233zd is a liquid blowing agent having a global warming potential (GWP) of less than 7, an ozone depletion potential (ODP) of about 0, an atmospheric lifetime of about 26 days, and a boiling point of about 19°C, and HFO-1234ze is a gaseous blowing agent having a global warming potential (GWP) of less than 6, an ozone depletion potential (ODP) of 0, an atmospheric lifetime of about 14 days, and a boiling point of about -19°C.
[0075] As another example, the butene is preferably a fluorochlorobutene.
[0076] As required, the blowing agent of the present disclosure may also include a blowing agent HFC having one to four carbon atoms. The blowing agent HFC may be, for example, selected from difluoromethane (HFC-32), fluoroethane (HFC-161), difluoroethane (HFC-152), trifluoroethane (HFC-143), tetrafluoroethane (HFC-134), pentafluoroethane (HFC-125), pentafluoropropane (HFC-245), hexafluoropropane (HFC-236), heptafluoropropane (HFC-227ea), pentafluorobutane (HFC-365), hexafluorobutane (HFC-356) and one or more of their isomers.
[0077] After the thermoplastic resin composition of the present disclosure is immersed in a blowing agent containing, for example, a fluoroolefin compound having 2 to 6 carbon atoms and having a global warming potential (GWP) of 1 and an ozone depletion potential (ODP) of about 0 at -40°C for 20 hours, the thermoplastic resin composition may exhibit a surface crack generation rate of 0%.
[0078] The thermoplastic resin composition of the present disclosure may have an Izod impact strength (ASTM D256), for example, greater than 20 kgf.cm / cm or greater than 20 kgf.cm / cm to 40 kgf.cm / cm.
[0079] The high temperature tensile strength (as an index of vacuum formability) of the thermoplastic resin composition of the present disclosure (measured at 150° C.) may be, for example, greater than 4.5 kgf / cm 2 Or greater than 4.5kgf / cm 2Up to 5.0kgf / cm 2 .
[0080] For example, the raw materials of the thermoplastic resin composition are first mixed in a mixer or a super mixer, and then fed into any one of a mixing processor such as a twin-screw extruder, a single-screw extruder, a roll grinder and a kneader. Alternatively, the raw materials are fed into any one of a mixer such as a twin-screw extruder and a kneader at a predetermined addition ratio. Then, melt kneading is performed at 200° C. to 300° C. to provide an extrusion molding having a desired shape, or particles are obtained. The obtained particles are fed again to an extrusion molding machine to prepare an extrusion molding. As required, the particles can be dehumidified or hot-air dried, and then injection molded. As a result, an injection molded product can be provided.
[0081] According to the present invention, there is provided a molded article comprising the above-mentioned thermoplastic resin composition.
[0082] The molded product may be an extruded sheet. For example, the molded product may be effectively used in various fields where a molded product is processed into a sheet shape, such as an extruded sheet for a refrigerator inner shell, a sheet for a refrigerator door, and a sheet for a general door.
[0083] Now, the present invention will be described in more detail with reference to the following preferred embodiments. However, these embodiments are provided for illustrative purposes only. It will be appreciated by those skilled in the art that various changes, additions and substitutions may be made without departing from the scope and spirit of the present invention. Therefore, it is apparent that these changes, additions and substitutions are within the scope of the present invention.
[0084] [Example]
[0085] Examples 1 to 3 and Comparative Examples 1 to 4
[0086] The ingredients summarized in Table 1 below were fed into a super mixer in the amounts disclosed in the table, and melt-kneaded at 230° C. using a twin-screw extruder, followed by extrusion processing. As a result, pellets were obtained. The pellets were used as samples for measuring properties.
[0087] The substances summarized in Table 1 below
[0088] (A) Butadiene graft copolymer: Average particle size 0.2 to 0.4 μm (Product name: DP270, manufactured by LG Chemistry)
[0089] (B) Acrylic acid graft copolymer: Average particle size 0.3 to 0.6 μm (Product name: SA927, manufactured by LG Chemistry)
[0090] (C) Vinyl cyanide-aromatic vinyl copolymer (SAN resin):97HC (made by LG Chemistry)
[0091] (D) Polyester elastomer (Thermoplastic polyester elastomer):
[0092] (D1) KEYFLEX BT 2140D (made by LG Chemistry): MI: 5 g / 10 min (230° C., 2.16 kg), Shore A hardness: 95, Shore D hardness: 43
[0093] (D2) KEYFLEX BT 1045D (made by LG Chemistry): MI: 25 g / 10 min (230° C., 2.16 kg), Shore A hardness: 95, Shore D hardness: 42
[0094] The average particle size was measured using a Nicomp 370 HPL according to a dynamic laser scattering method.
[0095] [Test example]
[0096] The properties of the samples respectively obtained according to Examples 1 to 3 and Comparative Examples 1 to 4 were measured by the following methods. The results are summarized in Table 1 below.
[0097] Performance measurement methods
[0098] <Chemical Resistance Test-Measurement of Changes in ESCR>
[0099] Each of the obtained samples was injection molded to prepare a sample for performance measurement. The injection molded sample was placed on a bending fixture with a strain of 0.7% and immersed in a HFO-1233zd (product name: Solstice LBA) foaming agent solution prepared by Honeywell. After 20 hours at -40°C, the generation of cracks on the surface was observed with the naked eye.
[0100] <Izod impact strength>
[0101] Each of the obtained specimens was injection molded to prepare a specimen (thickness: 1 / 4") for Izod impact strength measurement. The Izod impact strength of the prepared specimen was measured according to ASTM D256.
[0102] <Surface gloss>
[0103] Each of the obtained samples was molded into a sheet using a single screw extruder connected to a T-die at 230° C. The surface gloss of the obtained sample was measured at an angle of 60° according to ASTM D2457.
[0104] <Melt Index>
[0105] The melt index of the polyester-based elastomer is measured at 230° C. and a load of 2.16 kg according to ASTM D 1238. The melt index is expressed as the weight (g) of the polymer melted per 10 minutes.
[0106] <High temperature tensile strength>
[0107] Each of the obtained samples was injection molded into a size of 100 mm × 100 mm × 3.2 mm. The injection molded sample was cut into a size of 51 mm in total length, 15 mm in total width, and 6.5 mm in measurement portion width. After the cut sample was kept at 150° C. for 15 minutes, the high-temperature tensile strength of the cut sample was measured at a rate of 200 mm / min. Here, a higher tensile strength indicates excellent vacuum formability.
[0108] [Table 1]
[0109]
[0110] **: Parts by weight based on 100 parts by weight of the sum of the three copolymers indicated by *.
[0111] As shown in Table 1, it can be confirmed that in the case of Examples 1 to 3 according to the present invention, when used to manufacture the inner shell of a refrigerator, the molded article obtained from the thermoplastic resin composition provides higher chemical resistance to eco-friendly foaming agents while providing the same impact strength, glossiness and vacuum formability as the existing resin composition.
[0112] On the other hand, it was confirmed that, in the case of Comparative Examples 1 to 4, the glossiness, impact strength, and vacuum formability were inferior.
[0113] Additional Test Example 1
[0114] The same processing as in Example 1 was carried out except that the amount of the polyester elastomer (D) was 20 parts by weight.
[0115] As the results of the chemical resistance-ESCR change measurement, the surface crack generation rate was 0% (no cracks), the surface gloss (at 60 degrees) was 75, the Izod impact strength was 33kgf.cm / cm, and the high temperature tensile strength was 4.9kgf / cm 2 Therefore, it can be confirmed that the surface glossiness is inferior compared with Examples 1 to 3.
[0116] From these results, the present inventors confirmed that when a foam sheet made of a foaming agent having an ozone depletion potential (ODP) of 0 is mixed with an acrylic rubber other than a diene rubber and contains a specific polyester elastomer to apply the foam sheet to a substrate of an inner shell, a thermoplastic resin composition having a more stringent level of chemical resistance and providing the same impact strength, gloss and vacuum formability as existing compositions can be achieved.
Claims
1. A thermoplastic resin composition for a substrate of a polyurethane foam sheet, in, The polyurethane foam sheet is a polyurethane sheet foamed with a blowing agent containing a fluoroolefin compound having 2 to 6 carbon atoms and having a global warming potential (GWP) of less than 7, Wherein, the foaming agent comprising a fluoroolefin compound having 2 to 6 carbon atoms and having a global warming potential (GWP) of less than 7 is CF3CH=CHCl or CF3CH=CHF, Wherein, the thermoplastic resin composition comprises: 100 parts by weight of a base resin, the base resin comprising 10 to 35 weight % of a diene graft copolymer, 5 to 30 weight % of an acrylic graft copolymer, and 35 to 85 weight % of a copolymer of a vinyl cyanide compound and an aromatic vinyl compound; and 1 to 10 parts by weight of a polyester elastomer having a melt index of 0.1 to 5 g / 10 min measured at 230° C. and 2.16 kg according to ASTM D1238, The polyester elastomer comprises a branching agent, and the branching agent comprises one or more selected from glycerol, pentaerythritol, trimellitic anhydride, trimellitic acid, trimethylolpropane and neopentyl glycol. Wherein, based on the total weight of the polyester elastomer, the content of the branching agent is 0.05 wt % to 0.1 wt %, wherein, after the thermoplastic resin composition is immersed in a foaming agent represented by the formula CF3CH=CHCl or CF3CH=CHF at -40°C for 20 hours, the thermoplastic resin composition exhibits a surface crack generation rate of 0%, The diene graft copolymer is a copolymer prepared by grafting 30 wt % to 70 wt % of a diene rubber polymer and 30 wt % to 70 wt % of an aromatic vinyl compound and a vinyl cyanide compound, The acrylic graft copolymer is a copolymer prepared by graft polymerization of 30 wt % to 70 wt % of an acrylic rubber-like polymer; and 30 wt % to 70 wt % of an aromatic vinyl compound and a vinyl cyanide compound in total, and the acrylic graft copolymer has an average particle size of 0.3 to 0.6 μm, wherein the acrylic rubber-like polymer is a polymer formed by polymerizing an acrylic acid ester monomer, and The thermoplastic resin composition has a high temperature tensile strength of greater than 4.5 kgf / cm2 measured at 150°C. 2 .
2. The thermoplastic resin composition according to claim 1, wherein In the diene-based graft copolymer, the vinyl cyanide compound may be included in an amount of 20 to 40 wt % based on 100 wt % of the total of the compounds.
3. The thermoplastic resin composition according to claim 2, wherein The diene rubber-like polymer has an average particle size of 0.2 to 0.4 μm.
4. The thermoplastic resin composition according to claim 1, wherein In the acrylic graft copolymer, the vinyl cyanide compound may be included in an amount of 20 to 40 wt % based on 100 wt % of the total of the compounds.
5. The thermoplastic resin composition according to claim 1, wherein The acrylic graft copolymer may be included in an amount of 5 to 30 wt % based on 100 wt % of the base resin.
6. The thermoplastic resin composition according to claim 1, wherein The copolymer of a vinyl cyanide compound and an aromatic vinyl compound is a copolymer prepared by polymerizing 55 to 95 wt % of an aromatic vinyl compound and 5 to 45 wt % of a vinyl cyanide compound.
7. The thermoplastic resin composition according to claim 1, wherein The thermoplastic resin composition has an Izod impact strength greater than 20 kgf.cm / cm.
8. A molded product comprising the thermoplastic resin composition according to any one of claims 1 to 7, wherein: The molded article is an extruded sheet for an inner shell.
Citation Information
Patent Citations
Thermoplastic Resin Composition for RefrigeratorHaving Improved Environmental Stress Crack Resistance
KR1020060076161A
Styrenic resin composition
JP1999293085A